A 36 cm robotic optical telescope: Equipment and software - Sun, Jian; Cheng, Hao-Wen; Jiang, Hai; Liu, Jing; Zhao, Yuan-Yuan (Frontiers in Astronomy and Space Sciences, 2022)
The paper describes a set of optical telescope system and control software for robotic observation of space debris. The telescope has a main aperture of 355mm, adopts the optical design scheme of primary focus with a large field of view, and is equipped with a highly sensitive 4K sCMOS camera to achieve a large field of view of 2.6°×2.6°. The telescope is equipped with an environmental monitoring system and a highly reliable dome to ensure the safe operation of the telescope. The control software of the telescope consists of two parts. One part is deployed locally to comprehensively schedule the robotic operation of various equipment of the telescope system, and the other part is deployed remotely to realize the functions of equipment status monitoring, networking scheduling, remote control, and data management. At present, four telescopes have been deployed in Korla, Xinjiang, China to form a telescope array, basically realizing the remote "unattended" observation of space debris.